The beneficial effects of six weeks of swimming exercise on growth hormone and cortisol levels in male mice (Mus musculus) - Hilda Noor Dharmasanti; Purwo Sri Rejeki; Sulistiawati Sulistiawati; Shariff Halim; Muhamad Fauzi Antoni; Irmantara Subagio; Fajar Eka Samudra; Adi Pranoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to demonstrate the effects of moderate-intensity swimming exercise in the morning and evening over 6 weeks on the increase in growth hormone (GH) levels and the decrease in cortisol levels in male mice (Mus musculus). This research is a true-experimental study with a randomized control group posttest-only design. A total of 33 eight-week-old male mice (Mus musculus) weighing 20–40 grams were randomly divided into three groups: CN (n = 11; control without intervention), ME (n = 11; morning exercise), and AE (n = 11; afternoon exercise). Morning and evening exercises with moderate intensity were conducted for 30 minutes per session with a frequency of 3 times per week for 6 weeks. ELISA was used to evaluate posttest GH and cortisol levels in all samples. Data analysis was performed via one-way ANOVA, followed by Tukey’s honestly significant difference (HSD) post hoc test, with a significance level of p ≤ 0.05. The results revealed differences in the increase in GH levels between ME vs CN (5.71±0.88 vs 2.54±0.21 ng/mL, p=0.001), AE vs CN (7.18±1.66 vs 2.54±0.21 ng/mL, p=0.001), and AE vs ME (7.18±1.66 vs 5.71±0.88 ng/mL, p=0.009). Similarly, the decrease in cortisol levels differed among the ME vs CN (6.62±2.37 vs 10.69±4.38 ng/mL, p=0.004), AE vs CN (2.18±0.99 vs 10.69±4.38 ng/mL, p=0.001), and AE vs ME (2.18±0.99 vs 6.62±2.37 ng/mL, p=0.008) groups. This study revealed that both exercise durations significantly increased growth hormone levels and decreased cortisol levels in male mice (Mus musculus). However, evening exercise with moderate intensity was more effective at increasing growth hormone levels and decreasing cortisol levels than morning exercise with moderate intensity in male mice (Mus musculus).